EcoFarm: To encourage agroecological farming practices - Samaddar, Ayan; Subrata, Saha (2024)
A thorough understanding of natural mechanisms is essential for agroecology, a complicated method of conducting agriculture in harmony with nature. Our current work has attempted to comprehend this by employing the 13 principles of agroecology as the standard framework for evaluating the performance and providing necessary guidance for selected farming systems. It was discovered during this process that farmers need to be given the appropriate interpretation of these mechanisms to aid them in decision-making when engaging in agroecological practices. AI-driven methods have proven to be useful for helping farmers with precision farming methods. Predictive analytics and enhanced farm and crop management systems within an agroecological framework ensure crop quality and supply. Farmers should use the advantage of big data, AI, and ML technologies to predict prices, determine the health of the environment, and compute agricultural output and yield. The best crop kinds to plant for maximum profit, the optimal environmental conditions, the need for agricultural inputs (such as fertilizers, supplemental feed, etc.), and farming economics are all things it may advise farmers on. Since AI can optimize resource utilization and improve overall farm efficiency with exact awareness of limitations, difficulties, and driving forces, it will be a powerful tool that can assist organizations in navigating the increasing complexity of modern agriculture. In order to create a mobile application called EcoFarm, WorldFish and the University of Engineering and Management (UEM) have collaborated to use AI/ML technology. The goal is to support farmers who want to engage in agroecological farming in their decision making process. West Godavari district in Andhra Pradesh state, India, has been selected as the target site for the app's field-level experiment in order to assess its effectiveness and performance. Where farmers embraced integrated rice-fish farming under the Government of Andhra Pradesh's auspicious Andhra Pradesh Community Managed Natural Farming (APCNF) Initiative.